Genetic diversity and molecular analysis using RAPD markers of banana cultivars in the five regions of East Java, Indonesia - SLAMETO SLAMETO (Society for Indonesian Biodiversity, 2023)
Abstract. Slameto. 2023. Genetic diversity and molecular analysis using RAPD markers of banana cultivars in the five regions of East Java, Indonesia. Biodiversitas 24: 5035-5043. The study explored banana plants in East Java, Indonesia, specifically in the districts of Jember, Banyuwangi, Bondowoso, Situbondo, and Lumajang, using Random Amplified Polymorphic Deoxyribonucleic Acid (RAPD) markers. Thirty accessions of Musa ssp. were collected from these five districts, revealing a high level of genetic diversity. Primers OPA-04 and OPC-05 were suitable for assessing genetic variation in banana plants. It was found that the OPD-07 primer produced the fewest DNA bands (8 bands and 7 polymorphic bands), while the OPA-04 primer produced the maximum number of DNA bands (14 bands, with 9 polymorphic bands). The OPB-08 primer had the lowest polymorphism percentage (56%), and the OPC-05 primer had the greatest percentage (92%). With genetic similarity scores ranging from 0.04 (Bigih Tanjung Glugur and Lilin Banyuwangi) to 0.94 (Agung Banyuwangi and Let). The phylogenetic tree of 30 banana plants formed two primary clusters: cluster I and II, included 26 and 4 banana varieties respectively. In addition, molecular variance (AMOVA) resulted a significant proportion (93%) of genetic diversity within the population. Further studies using more precise genetic markers are still needed to determine the exact identity of the banana plant genome.